PENGARUH PENDAPATAN ASLI DAERAH (PAD), DANA ALOKASI UMUM (DAU), DAN SISA LEBIH PEMBIAYAAN ANGGARAN (SiLPA) TERHADAP BELANJA MODAL KABUPATEN/KOTA SE-JAWA TIMUR (APBD Tahun Anggaran 2016) - Okynawa, Sandra; Sulistyo, Sulistyo; Mustikowati, Rita Indah (Fakultas Ekonomi Universitas Kanjuruhan Malang, 2018)
The enactment of Law Number 32 of 2004 concerning Regional Government is a sign of the commencement of regulations on regional independence or regional autonomy, where regional governments have the responsibility and authority in managing and regulating their own regional interests and progress. Thus each regional government must be able to develop and provide adequate services for the region so that from the development that has been carried out by the region will be able to contribute to the utilization of every revenue in the budget. The implementation of the decentralized system requires each region to prepare a budget plan that is commonly called the Regional Revenue and Expenditure Budget (APBD), where the APBD is a projection of each income and expenditure budget that is obtained and released by the government for one future budget. One important expenditure item in the Regional Budget is Capital Expenditures. Capital expenditure post allocation is a reflection of revenue allocation that is expected to be able to meet demands for public services. This study aims to project how much influence the independent variable (Regional Original Income, General Allocation Funds, and SiLPA) on the dependent variable (Capital Expenditure in the Regency / City in East Java) for the 2016 State Budget.Data collection techniques used documentation and literature study techniques, with a total sample of 38 samples. The method used Multiple Linear Regression analysis, where the test results are simultaneously known PAD, DAU, and SILPA variables affect the district / city capital expenditure in East Java, as well as partially note that the PAD, DAU, SiLPA variables affect Capital Expenditure Regency / City Capital in East Java.